URINE SPECIMEN IN DETECTION OF HEPATITIS A VIRUS ANTIBODY IN CHILDREN - Setyoboedi, Bagus; Sukmawardani, Maretha; Arief, Sjamsul (Institute of Topical Disease Universitas Airlangga, 2010)
Hepatitis A is still a problem in developing country, especially in Indonesia. Twenty-three thousand cases per year in the world were reported by CDC in 1998. Detection of Hepatitis A Virus (HAV) antibody needs blood specimen, for which the drawing procedure is quite unpleasant for children. The purpose of present study is to examined the use of urine as an alternative specimen compared to blood in the detection of HAV antibody. A cross sectional study on children age 5–12 years who lived in Rusun Sombo District Simokerto Surabaya was performed in 2007. Blood and urine specimens were taken from all subjects, further tested with Microparticle Enzyme Immunoassay (MEIA) method using AxSym® HAVAB® 2.0. A total 74 children were included in the study, 43 (58.1%) were boys. Seropositive was found in 38 (51.4%) children and uropositive in 3 (4%) children. There are significant differences between blood and urine specimen, with sensitivity 7.9%, spesificity 100%, PPV 100% and NPV 50.7%. Urine could not replace blood specimen as the gold standart for the detection of hepatitis A antibody in children